2018
DOI: 10.1177/1464419318762678
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear dynamic response analysis of cylindrical roller bearings due to rotational speed

Abstract: The dynamic behaviour of cylindrical roller bearings is presented, in both balanced and unbalanced conditions as a function of speed. The stiffness and damping non-linearities at the contact points (due to Hertzian contact force between rollers and races), radial internal clearance and unbalanced rotor force make the bearing system non-linear. Presently, the differential equations representing the dynamics of the cylindrical roller bearings have been obtained using Lagrange’s equation and solved numerically us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Zhuo et al 10 performed a study on the dynamic behavior of the self-aligning ball bearing and conducted a parametric study on several parameters like applied loads, internal clearance etc. Patra et al 11 performed a study on the nonlinear dynamic response on the cylindrical roller bearing due to fluctuation in speed and load, the analysis was helpful for online monitoring of fault-free cylindrical roller bearings and for studying the impact of speed on system's dynamical behavior Petersen et al 12 performed an analysis on the variation of stiffness and contact forces of a defective self-aligning ball bearing. They compared the variation of these parameters in the case of dynamic and quasi-static conditions.…”
Section: Elastic Deformation and Time-varying Stiffnessmentioning
confidence: 99%
“…Zhuo et al 10 performed a study on the dynamic behavior of the self-aligning ball bearing and conducted a parametric study on several parameters like applied loads, internal clearance etc. Patra et al 11 performed a study on the nonlinear dynamic response on the cylindrical roller bearing due to fluctuation in speed and load, the analysis was helpful for online monitoring of fault-free cylindrical roller bearings and for studying the impact of speed on system's dynamical behavior Petersen et al 12 performed an analysis on the variation of stiffness and contact forces of a defective self-aligning ball bearing. They compared the variation of these parameters in the case of dynamic and quasi-static conditions.…”
Section: Elastic Deformation and Time-varying Stiffnessmentioning
confidence: 99%
“…The other peak that contributes significantly to the frequency responses is '6(VC þ X)/9'. Patra et al 33 showed the relation for the dynamic behavior of cylindrical roller bearings with an unbalanced rotor condition as a function of speed which is effective for all the clearance range. Table 3 presents the change in frequency responses of the cylindrical roller bearings due to variation in radial load.…”
Section: Effect Of Radial Internal Clearance On Dynamic Conditionmentioning
confidence: 99%
“…It could be restrained by eccentricity incentives under high speed. 32 Patra et al 33 found that there was an interaction between VC and unbalanced force. Meyer et al 34 indicated that the outer ring rotating frequency generated by the outer race misalignment would modulate nN b f c , leading to the generation of side frequencies.…”
Section: Introductionmentioning
confidence: 99%